O coordenador pedagógico como agente da formação teórica continuada dos professores - Molla, Sandra Regina Petrone (2013)
This research had as its object the role of Pedagogical Coordinator in further theoretical training of teachers in school units. The problem investigated in the context of this object, was: what is the role of the Pedagogical Coordinator in further theoretical training of teachers within schools? Were sought answers to the following questions: What theoretical understand why the educator? What is theory and that theory? What is the role of theory in educational practice? What role can the pedagogical coordinator in further theoretical training of teachers in schools? Aimed to provide subsidies for both the formation of pedagogical coordinator, how to develop their role to promote the continuity of theoretical training of teaching staff in schools. Literature was developed and the results were presented in the chapters of the dissertation. Positions were identified concerning this function Pedagogical Coordinator and tried to indicate ways how he can do it. It was clear that the privileged place of continuing education is the school because it is the locus where knowledge and experience are experienced, rejected, validated and appropriate and that it is the Pedagogical Coordinator engage and involve teachers in this aspect of their training. It was found that there is consensus on this assignment Coordinator, both by legal provisions, as by researchers who are dedicated to studying the role of this professional. But, it was also found that there are few studies specifically related to their role in the processes of theoretical continuing teachers. This requires extension of these studies.